2020
DOI: 10.1021/acs.energyfuels.0c00274
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance, Biobased, Jet Fuel Blends Containing Hydrogenated Monoterpenes and Synthetic Paraffinic Kerosenes

Abstract: Three biorenewable monoterpenes, α-pinene, limonene, and sabinene, were hydrogenated to generate cycloalkane blendstocks. The saturated terpenes, along with the high density multicyclic fuels JP-10 and RJ-4, were then blended with three different synthetic paraffinic kerosenes (SPKs) in various proportions. The SPKs consisted of HEFA-Jet (a complex mixture of acyclic hydrocarbons generated by hydrotreatment of fatty acids and esters), 5-methylundecane (5-MU, a C 12 hydrocarbon that can be generated from bioeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…DMCO exhibited a density of 0.827 g mL −1 at 15 °C. This value is 6.7 % higher than the lower limit for conventional jet fuel (0.775 g mL −1 ) and 12.8 % higher than the acyclic hydrogenated isoprene dimer 2,6‐dimethyloctane (0.73 g mL −1 ) [27] . The gravimetric and volumetric NHOCs of DMCO were 43.822 MJ kg −1 and 36.222 MJ L −1 , respectively.…”
Section: Bio‐based Alkenesmentioning
confidence: 75%
See 3 more Smart Citations
“…DMCO exhibited a density of 0.827 g mL −1 at 15 °C. This value is 6.7 % higher than the lower limit for conventional jet fuel (0.775 g mL −1 ) and 12.8 % higher than the acyclic hydrogenated isoprene dimer 2,6‐dimethyloctane (0.73 g mL −1 ) [27] . The gravimetric and volumetric NHOCs of DMCO were 43.822 MJ kg −1 and 36.222 MJ L −1 , respectively.…”
Section: Bio‐based Alkenesmentioning
confidence: 75%
“…This value is 6.7 % higher than the lower limit for conventional jet fuel (0.775 g mL À 1 ) and 12.8 % higher than the acyclic hydrogenated isoprene dimer 2,6-dimethyloctane (0.73 g mL À 1 ). [27] The gravimetric and volumetric NHOCs of DMCO were 43.822 MJ kg À 1 and 36.222 MJ L À 1 , respectively. These values are up to 2.4 % and 9 % higher, respectively, than conventional jet fuel (Table 10).…”
Section: Bio-based Alkenesmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, recent studies have shown that 30 % cycloalkane blends have the same swelling capability as low (8 %) aromatic fuel blends [20–23] . Cycloalkanes also have higher densities due to their constrained geometries, and significantly higher volumetric NHOCs than SPKs and traditional jet fuels [17] …”
Section: Introductionmentioning
confidence: 92%